System Development of an Autonomous Lawnmower System Using Ardupilot Mission Planner - ABDUL RAHIM, MUHAMMAD SYAZWAN AZIZI; JOHAR, Ts. Dr. MUHAMMAD AKMAL (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This research focusses on the development of an autonomous system for a lawnmower, abandonment of cutting grass due to Covid-19 that impacts the social interactions between humans. Hence, by building an autonomous lawnmower, less worker leads to less interactions between humans that will also save time and labour cost. The main objective is to build simulate an autonomous system using Ardupilot Mission Planner by studying the system and choosing the best solution. This research will fully be conducted using Ardupilot Mission Planner as its system and the simulation. This research are conducted to run a grid pattern for lawn mowing.In conclusion, this research will resulted the effectiveness of different grid pattern and several data gathered from several parameter. Some recommendation for future works is to do experimental testing in real life and for simulation is to include environmental factors to achieve more precision result.